A Meta‐Analysis of Newsvendor Experiments: Revisiting the Pull‐to‐Center Asymmetry. Issue 1 (9th July 2018) - Zhang, Yinghao; Siemsen, Enno
Abstract : The field of behavioral operations has produced a rich tradition of experiments in newsvendor decision‐making. Our study provides a meta‐analysis of 24 papers in this research area; we confirm that the pull‐to‐center (PtC) effect, where average order quantities in a sample lie in between average demand and optimal order quantities, is a very stable observable phenomenon across studies. However, we also show that the asymmetry in the PtC effect between high‐margin and low‐margin conditions varies significantly from study to study; factors that allow predicting the extent and direction of the PtC asymmetry include the likelihood of obtaining losses, the way underage costs are presented to subjects, and the existence of a decision support system. We validate these factors using a controlled experiment. In conclusion, the PtC asymmetry appears less as a fundamental attribute of human behavior, but rather as a function of the design aspects of the experiment.